Management of Kindergarten (TK) Parenting Program in Mujahidin 2 on East Pontianak District - Eni Utami; Wahyudi Wahyudi; Fadila Fadilah (STKIP Singkawang, 2018)
Parenting program is an educational effort implemented by the family by utilizing the resources available in the family and the environment in the form of between the care of the family with the care of the school so that the growth and development of learners can be optimal. This study aims to 1) Describe the planning parenting program of Kindergarten (TK) of Mujahidin 2 East Pontianak District, 2) To describe the implementation of a parenting program in Kindergarten of Mujahidin 2 East Pontianak District, 3) To describe the evaluation of the parenting program of Kindergarten of Mujahidin 2 Eastern Pontianak District. This research uses the descriptive method with a qualitative approach. The focus of this research is the management of parenting program of Kindergarten (TK) on aspects of planning, implementation, and evaluation. The technique of collecting data using interview, observation, and documentation. The result of the research are 1) parenting program planning conducted by theprincipal, educators and parent representatives as well as the planning that is compiled still refers to the school program and based on the educational calendar. 2) Implementation of parenting program is evident with the cooperation between principal, educators, and parents for both the required funding issues and the mean of infrastructure used. 3) The evaluation of the parenting program is carried out internally by the principal and educators and implemented after the program is completed.